Mental health and addictions policy priorities and performance measurement frameworks. Issue 2 (March 2019) - Sirotich, Frank; Adair, Carol E.; Durbin, Janet; Lin, Elizabeth; Canning, Christopher
To inform the future development of a pan-Canadian Mental Health and Addictions (MHA) performance measurement framework, we undertook a review and comparison of current provincial/territorial MHA policies and performance measurement frameworks. Most did not have performance measurement approaches that were explicitly linked to policy actions but eleven acknowledged the importance of performance measurement. Among the provinces with a framework, there were few performance domains in common. The common policy priorities and areas of convergence in current performance measurement practices may provide a useful starting point for the development of a pan-Canadian MHA performance measurement framework.